Transdisciplinarity and the Curriculum: Reading UNESCO’s “Reimagining Our Futures Together” with Transdisciplinarity in Mind - Radakovic, Nenad (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2023)
This paper delves into the concept of transdisciplinarity and its potential application in education by conducting a critical analysis of UNESCO's report titled "Reimagining Our Futures Together: A New Social Contract for Education." The report emphasizes the pressing need to address existential risks and climate change, thereby advocating for transformative educational practices. The paper explores the historical development of transdisciplinarity, encompassing structuralist-systems, holistic, and postmodern approaches. Using a transdisciplinary lens, the study examines crucial themes from the UNESCO report, including ecological, intercultural, and interdisciplinary learning integration, the concept of the Knowledge Commons, and the proposition for a new social contract between individuals and governments. This examination serves as an exemplar of how to interpret and question educational texts through a transdisciplinary perspective.